AN EFFICIENT GREEN DISTRIBUTION ROUTE USING SAVING MATRIX METHOD AT PT. ASAHIMAS FLAT GLASS CIKAMPEK FACTORY - Milzam Abdurrahman, Muhammad
PT Asahimas Flat Glass has challenges in improving quality in terms of distribution distance, time, and cost without reducing the quality of goods. PT Asahimas Flat Glass targets for finished goods distribution costs to be no more than 1.5% of overall operating costs. The initial percentage of finished goods distribution costs compared to operating costs is 1.58%. One of the efforts that can be made is to organize a good distribution pattern, this will have a big impact because this pattern will be used every day. This research develops distribution route improvement at PT Asahimas Flat Glass, Cikampek Factory, using the Saving Matrix method. The purpose of this research is to improve the efficiency of the distribution process by considering travel distance, travel time, transportation cost, and total carbon emission. This study detected considerable inefficiencies in the initial distribution route. The analysis showed a 5.81% reduction in total travel distance from 13,752,960km/year to 12,954,559km/year. Travel time efficiency of 2.24% from 200,280 hours/year to 195,792 hours/year. Distribution cost efficiency of 9.19% from Rp66,950,772,480/year to Rp60,796,461,033/year. In addition, the new distribution route also resulted in a reduction in total carbon emissions by 5.81% from 18,429 tons/year to 17,359 tons/year, which is in line with PT Asahimas Flat Glass' sustainability goals. The findings in this study show how effective and efficient this method is in creating a more cost-effective and environmentally friendly distribution route. Recommendations include implementation at other plants, monitoring and adjustment, employee training, and investment in technological automation. Further research can focus on integrating different improvement algorithms and realizing increased efficiency levels in distribution.